STUDENTS’ EXPERIENCES IN USING GOOGLE SITES E-PORTOFOLIO FOR LEARNING ACCOUNTING VOCABULARY - Musdalifah; Abdul Karim; Chaerul Fadlan Saud (Program Studi Pendidikan Bahasa Inggris, 2025)
Digital learning innovations have increasingly transformed English for Specific Purposes (ESP), particularly in promoting learner autonomy, engagement, and reflection. Among these innovations, e-portofolios have been recognised as powerful tools for integrating language learning with professional skills. However, previous research has primarily focused on e-portofolios in writing and general English context, while limited attention has been given to their use in teaching accounting vocabulary, where learners often struggle to understand and retain specific terminology. This gap between theoretical expectations and classroom realities highlights the need to explore how e-portfolios can facilitate vocabulary learning in ESP courses. This study aims to investigate student’s experience with Google Sites e-portofolios for learning accounting vocabulary in an English for Accounting course at Bahasa Inggris Program Sarjana Terapan Study Program, Universitas Negeri Makassar. Employing a qualitative descriptive design, the data were gathered from eight students through semi-structured interviews and analysed thematically. The findings revealed that students' first impressions were characterised by enthusiasm, curiosity, and a motivation to use Google Sites as an innovative learning platform. The process of creating and managing e-portfolios fostered creativity, organisation, and digital literacy, as students designed pages and linked vocabulary items to authentic accounting materials. Students perceived several benefits, including improved understanding and retention of accounting terms, enhanced confidence, and a stronger connection between academic learning and professional application. Despite minor challenges such as technical issues and time constraints, participants regarded e-portfolios as engaging and valuable learning tools. The study concludes that Google Sites e-portfolios effectively promote learner autonomy, reflection, and engagement in English for Specific Purposes (ESP) context. It is recommended that future ESP instruction provide technical orientation and continuous support to maximise the benefits of e-portfolios in language learning.